1995
DOI: 10.1177/43.10.7560881
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of osteogenic protein-1 (bone morphogenetic protein-7) in human and mouse development.

Abstract: Osteogenic protein-1 (OM; BMP7) is a member of the bone morphogenetic protein subfamily. Because members of the TGF-p superfamily have a role in tissue development, the distribution of OP1 expression in developing human embryos (5-8 gestational weeks) and fetuses (8-14 gestational weeks) and mouse (9.5-17.5 gestational days) fetuses was examined. Northern hybridization with specific OB1 probes revealed two mRNA species of 4 and 2.2 KFI. Highest levels of OP1 mRNA were found in human fetal kidney and heart betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
114
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(127 citation statements)
references
References 8 publications
11
114
0
2
Order By: Relevance
“…Although BMP-7 was originally identified as a protein that induced bone and cartilage formation, with an important role in the morphogenesis of embryo and in postnatal life (37), it is also produced in kidney (37,38). Recent studies have shown that BMP-7 is able to prevent kidney damage in vivo in numerous animal models of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMP-7 was originally identified as a protein that induced bone and cartilage formation, with an important role in the morphogenesis of embryo and in postnatal life (37), it is also produced in kidney (37,38). Recent studies have shown that BMP-7 is able to prevent kidney damage in vivo in numerous animal models of disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are expressed in a wide range of non-skeletal tissues during mammalian development, including germ layer, whiskers, hair, teeth, urogenital system, gut, heart and brain (170,171). These observations suggest that BMPs have a much broader role in overall tissue morphogenesis, and in repair of other tissue systems.…”
Section: Other Areas Of Potential Clinical Use Of Bmpsmentioning
confidence: 99%
“…Bone morphogenetic protein 7 (BMP-7), a member or the transforming growth factor-␤ (TGF-␤) superfamily, is widely expressed during embryonic growth (15) and is an essential morphogen in renal, skeletal, and eye development (16 -18). The BMP-7 null mouse dies of perinatal renal failure due to hypoplastic dysplastic kidneys.…”
mentioning
confidence: 99%